Analisis Penerapan Kesehatan dan Keselamatan Kerja Pada Lingkungan Kerja di Cofee Shop +62 - Rizki Gumilang Sutisna; Asep Erik Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
As time goes by, the number of coffee enthusiasts in Purwakarta City has increased, thus creating many coffee shops that have been established in Purwakarta City. This of course creates competition between these coffee shop service providers to provide the most comfortable place possible and provide attractive coffee menus to attract consumers. To attract consumers to visit, coffee shop service providers must offer coffee or food menus with the characteristics of the coffee shop, these characteristics will be remembered by consumers who have visited, and do not rule out visiting again. To be able to provide the best service to consumers, coffee shop service providers must have facilities such as good physical facilities, a good work environment and aspects of occupational health and safety (K3). This must be done so that consumers feel comfortable when visiting and employees who work can be comfortable while working and will feel safe so as to avoid all diseases and accidents in the workplace. This research is about the application of occupational health and safety in coffee shop 62 and this research is descriptive. The purpose of this study is to find out how the implementation of K3 in the coffee shop. The technique of collecting data from this research is by direct observation and conducting direct interviews with the owner and the employees who work.